Trinidad and Tobago. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Trinidad and Tobago during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as public policies, agricultural health, good manufacturing practices, biotechnology, biosafety, methodologies and food safety. , through the Codex Alimentarius. Finally, it relied on the inclusion of women, on improving the value chains of fruits, goat milk, roots, tubers, vegetables, meat and sheep, and on pest control, such as black sigatoka.